JUSTIFICATION OF THE INFLUENCE OF FERTILIZERS ON THE PRODUCTIVITY AND QUALITY INDICATORS OF SPRING WHEAT GRAIN - Кудрявицька, Аліна; Карабач, Катерина (Modern engineering and innovative technologies, 2023)
Studies on the meadow chernozem is installed that systematic using the mineral fertilizers on background of the aftereffect organic, provides the gain of the harvest grain sort of the spring wheat мironovskaya - bright on 1,73 t/he. The productivity and q